From Blackouts to Breakthroughs: Examining Electricity S Relevance in Healthcare During Covid-19 and the Future Role of Renewable Energy - Escobar, C (Elsevier Ltd, 2023)
Power supply played a critical role during the COVID-19 pandemic in keeping hospitals and critical medical equipment operating, which was quickly reflected in electricity consumption and new consumption patterns. However, not all countries faced the same challenges. While developed countries could react adequately to changes in hospital electricity consumption patterns, low-income countries faced infrastructure and energy access challenges during the pandemic, which hampered the management of the pandemic in all of its dimensions. This paper reviews the importance of power supply in hospitals through a literature review and divides the discussion into three sections. First, the factors influencing new hospital consumption patterns during the pandemic are discussed. Then, the consequences of the lack of electricity in remote areas on managing the pandemic are reviewed. Finally, the impact of the pandemic on the design of hybrid power generation systems is reviewed, which must not only provide autonomy for similar future scenarios but also be prepared to respond to sudden increases in power consumption due to a greater number of patients or longer working hours, an increase in the number of critical loads, and possible restrictions on access to fuel. Thus, this work provides valuable insights for policymakers, academics, and researchers on the importance of updating hospital power supply standards and contributes to demonstrating the need to electrify remote hospitals. © 2023 Elsevier Ltd